2011
DOI: 10.1161/hypertensionaha.111.180497
|View full text |Cite
|
Sign up to set email alerts
|

Description of Antihypertensive Use in Patients With Resistant Hypertension Prescribed Four or More Agents

Abstract: Abstract-Data describing the use of recommended antihypertensive agents in the resistant hypertension population are limited. Treatment recommendations for resistant hypertension include maximizing diuretic therapy by using chlorthalidone and/or adding an aldosterone antagonist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
2
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 30 publications
5
51
2
3
Order By: Relevance
“…These results are consistent with previous cross-sectional studies in the TRH population. 17,18 Using data from the National Ambulatory Medical Care Surveys, Fontil et al 19 observed nonsignificant increases between 2006 and 2010 in the use of β-blockers, CCBs, and aldosterone receptor antagonists, similar to the trends found in our study. In contrast, the authors saw thiazide diuretic use decrease slightly during the study period, whereas we observed no substantial change in the prevalence of thiazide diuretics among TRH regimens.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These results are consistent with previous cross-sectional studies in the TRH population. 17,18 Using data from the National Ambulatory Medical Care Surveys, Fontil et al 19 observed nonsignificant increases between 2006 and 2010 in the use of β-blockers, CCBs, and aldosterone receptor antagonists, similar to the trends found in our study. In contrast, the authors saw thiazide diuretic use decrease slightly during the study period, whereas we observed no substantial change in the prevalence of thiazide diuretics among TRH regimens.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies from 2010 and earlier have suggested similarly low use of chlorthalidone (1.4% of all office visits for patients with TRH, or 3% of all patients with TRH). 17,19 Use of indapamide was even lower in our study (<1%), which may be related, in part, to our younger (<65 years) study population. Whether indapamide use would have been greater in an older population (eg, as enrolled in the Hypertension in the Very Elderly Trial 26 ) is not known.…”
Section: Discussioncontrasting
confidence: 50%
“…2 A study of pharmaceutical and claims data reported a 5.9 % use of aldosterone antagonists and 3 % use of chlorthalidone among resistant hypertension patients taking ≥ 4 medications. 20 Our study extends the current literature in a few additional ways. We examined trends in treatment of resistant hypertension after publication of the AHA recommendations, showing no increase in physician prescribing of recommended medications for resistant hypertension.…”
Section: Discussionsupporting
confidence: 70%
“…Defined as failure to achieve a BP goal of <140/90 mm Hg, despite treatment with ≥3 different antihypertensive medication classes at a maximally tolerated dose and, including a diuretic, recent trials of resistant hypertension have shown some success with the inclusion of darusentan, an endothelin A antagonist or the aldosterone antagonists spironolactone or eplerenone, although the latter are underused in practice. 1,2 However, most interest in the management of resistant hypertension has been on interventions that target the sympathetic nervous system, especially devices. Catheter-based renal denervation procedures and carotid baroreceptor stimulation have been the subject of intense investigation with early reports of dramatic improvement of BP control.…”
Section: Resistant Hypertensionmentioning
confidence: 99%